Enhanced Photocatalytic Activity: Macroporous Electrospun Mats of Mesoporous Au/TiO2 Nanofibers. Issue 9 (5th June 2013) - Wang, Xingdong; Choi, Jonghyun; Mitchell, David R. G.; Truong, Yen B.; Kyratzis, Ilias L.; Caruso, Rachel A.
Abstract An electrospinning technique coupled with sol–gel chemistry is applied for the one‐pot preparation of macroporous–mesoporous titanium dioxide nanofibrous mats embedded with Au nanoparticles. This facile approach produces nanofibers that are thermally treated to simultaneously 1) remove the organics, 2) reduce AuIII to Au0 to form Au nanoparticles, and 3) crystallize titania to the anatase phase. This methodology allows high‐temperature treatment (650 °C) for well‐crystallized titania without agglomeration of the nanoparticulate Au (13±3 nm), which thereby significantly advances the existing methods for the synthesis of Au/TiO2 materials for which multiple steps are required. Additionally, high Au yields (≈100 %) were achieved in the final structure, which demonstrates another merit of this technique. The X‐ray diffraction patterns of the nanofibers were monitored by using a synchrotron beamline as the sample was heated to determine the optimum calcination temperature required to maximize the anatase phase and minimize the formation of rutile. Both the material properties (which include morphology, pore size distribution, surface area, Au particle size, and TiO2 crystal phase and size) and photocatalytic activity can be readily tuned as a function of the calcination temperature and Au content. The material calcined at 550 °C with 2.0 wt % Au shows the highest photocatalytic activity. This material is anatase in phase (which maximizes the electron‐transfer activity) and has the highest loading of small Au nanoparticles (which act as electron sinks to decrease the recombination of photo‐excited electrons and holes). These Au/TiO2 nanofibrous mats have the advantage of easy recovery and, therefore, reuse after the photocatalytic reaction, which addresses the issue of photocatalyst separation when using nanoparticulate powders as photocatalysts.